(untitled) (Research, Society and Development, 2020)
Toxicity cases from the agribusiness field are classified by SINITOX as a single category (exogenous intoxications). Although the accidental route to exogenous intoxications is more common, national data indicate that self-induced intoxication is the main means used. This research was to estimate exogenous intoxications by veterinary products in the Information System for Notifiable Diseases (SINANNET) in the northeastern region of the state of Paraíba between the years 2013 and 2017. A retrospective analysis was carried out, descriptive and quantitative, with further study of the variables relevant to the intoxicated and drug poisoning. Among the 99 notifications, the male gender predominated (53.53%), the age group of 20 to 39 years (34.34%), the urban residential area (76.77%) and the incomplete elementary school of the 5th the 8th (11.11%). In addition, a significant amount of intoxicants (79.80%) evolved to cure without complications, representing 79 of the total. In contrast, there was no death from exogenous intoxication. Therefore, proposing to reduce the number of occurrences, means of spreading information to the population must be implemented with diligent methods of instruction to professionals in animal health and the veterinary products industry.